EXPERIMENTS ON COLD-FORMED STEEL LIPPED CHANNEL COLUMNS WITH END-TRACK IN COMPRESSION - Hiranmarn, Watanapong; Chomchuen, Prakit; Nuttayasakul, Nuthaporn (วารสารวิชาการ โรงเรียนนายร้อยพระจุลจอมเกล้า, 2014)
-